2010
DOI: 10.1007/s11136-010-9796-0
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric properties of the Spanish form of the schedule for meaning in life evaluation (SMiLE)

Abstract: The results support the validity of the Spanish version of the SMiLE as an instrument for assessing meaning in life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 22 publications
2
7
0
Order By: Relevance
“…The MiL indices derived from application of the SMiLE (Table 2) to Spanish PC patients are generally high and similar to those obtained in other studies of both healthy individuals 6,20,23 and PC patients. 6,7,21 In terms of the areas that contribute to MiL (Table 3), family was by far the most frequently listed area (89.1% of patients).…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…The MiL indices derived from application of the SMiLE (Table 2) to Spanish PC patients are generally high and similar to those obtained in other studies of both healthy individuals 6,20,23 and PC patients. 6,7,21 In terms of the areas that contribute to MiL (Table 3), family was by far the most frequently listed area (89.1% of patients).…”
Section: Discussionsupporting
confidence: 82%
“…This was followed at a considerable distance by the areas partner (41.6%), well-being (40.6%), and friends (30.7%). Comparing these results with those obtained in a sample of healthy Spanish university students, 23 we found that the university students also listed family as the first area of meaning (99.5%). However, in the case of the students, the second most listed area was friends (80.7%), the third work (76%), and the fourth well-being (59.6%).…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…The meaning of life, another element of the theme ‘loss of self’, has recently attracted considerable interest among clinicians and researchers in the field of palliative care, and has become a key element of certain psychotherapeutic interventions [33], [39], [77]. Those patients who, despite their illness, continue to feel that life is meaningful are able to regard their life as worth living [78].…”
Section: Discussionmentioning
confidence: 99%
“…Factors addressed by research include pain [28], [29], depression [20], [30], [31], hopelessness [32], [33], [34], the feeling of being a burden [12], [34], [35] and loss of autonomy [28], [36], [37]. Various socio-cultural aspects may also play an important role in relation to the origin of such a wish, for example, family and social support or factors related to what gives meaning to life [38], [39], [40]. In general, clinical studies highlight a multi-factor aetiology, and the evolving literature on the WTHD points — perhaps in line with improvements in the treatment of physical pain — toward the considerable influence of other factors related with the spiritual and psychological dimensions of the individual [13], [14], [41], [42].…”
Section: Introductionmentioning
confidence: 99%